Worldwide Developments in Sports Biomechanics Investigation: Consequences for Injury Avoidance, Athlete Efficiency, and Recovery Scopus Bibliometric Examination - Akhmad, Noor; Maulidin, Maulidin (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives.. This investigation seeks to delineate worldwide patterns in sports biomechanics through the application of bibliometric analysis. This study centers on the geographical distribution, contributions from institutions, collaborations among scholars, and the identification of significant and emerging themes related to biomechanics, injury prevention, athlete performance enhancement, and rehabilitation. This method offers a comprehensive perspective on fostering scientific partnerships and advancements in the field of sports biomechanics. Materials and Methods.. The Scopus database was utilized to gather data from 2014 to 2024, yielding 615 articles following a screening process of 1,139 initial documents. The analysis of data was conducted utilizing VOSviewer and Biblioshiny software to illustrate the connections among authors, institutional contributions, and research themes. Data cleaning was conducted with OpenRefine to eliminate duplications and standardize formats. The analysis encompasses the distribution of studies across various countries, key themes, and emerging trends to gain insights into the trajectory of biomechanics research advancement. Results. The findings indicate that the United States, United Kingdom, and Australia lead in sports biomechanics publications, with notable contributions from institutions like the University of North Carolina and the Michel Center for Sports Injury Prevention. Fundamental areas like Sports Biomechanics, Injury Prevention, and ACL continue to be prioritized, while new developments in AI and Subconcussion highlight innovative advancements. Analysis of the network indicates the presence of research clusters focused on knee and head injuries; however, there is a need for enhanced collaboration across different themes. Conclusions. This study offers valuable insights into the priorities of sports biomechanics research, emphasizing the significance of incorporating contemporary technologies like AI and wearable sensors to enhance injury prevention, rehabilitation, and athlete performance. The findings are significant in advancing the creation of safer and more inclusive training policies, particularly for groups like female athletes who have distinct requirements.